Adopting E-learning in Academic Accounting Programs from the Perspective of Faculty Members in Sudanese Public Universities - Fatihelelah Mohammed Ahmed Mohammed; Alsharif Elhussein Awad Elamin (University of Science and Technology, Yemen, 2021)
The adoption of e-leaning in higher education in Sudan is one of the challenges of post-Coronavirus Pandemic. This study aimed to identify the reality of adopting e-learning in academic accounting programs in Sudanese public universities. To achieve this objective, the descriptive mothed was used; and a questionnaire for collecting relevant data was administered to a sample of (135) faculty members of accounting programs at 17 public universities in different states of Sudan. The study findings showed that the faculty members have sufficient knowledge of e-learning and the benefits of using it in teaching and learning. The faculty members' sufficient level of knowledge of in e-learning had a clear impact on building sufficient conviction towards the adoption of e-learning and using it in the curricula of the accounting programs. There was also a relationship between the faculty members' level of knowledge of e-learning and their knowledge of the requirements for adopting e-learning. In addition, there was a relationship between the requirements of the application of e-learning and the obstacles, as the requirements of the application constitute real obstacles that prevent the adoption of e-learning in accounting programs. The study recommended that the ministry of higher education should have a clear vision towards the adoption of e-learning to be gradually implemented by using a blended system of education (electronic & traditional) in order to prepare and equip students with e-learning skills.